1999
DOI: 10.1111/jon199992102
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Benefit of Echocontrast Enhancement for the Insufficient Transtemporal Bone Window

Abstract: Echocontrast agents (ECA) are known to improve transcranial color-coded duplex (TCCD) imaging, but its diagnostic benefit in the routine clinical setting has not clearly been defined. The authors investigated the diagnostic benefit of ECA application in 54 patients with insufficient transtemporal bone window, consecutively referred to their ultrasound laboratory. According to the precontrast imaging quality, patients were assigned to three categories: A, no intracranial structures or vessel segments visible on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…This is in line with previous studies 1,4,19,20 that analyzed the benefit of UCA application during transtemporal insonation with TCCD. An improvement in the signal quality for the posterior circulation after application of UCA 8,9 was also reported, although the BA could be visualized only over a mean distance of 1.7 cm.…”
Section: Discussionsupporting
confidence: 80%
“…This is in line with previous studies 1,4,19,20 that analyzed the benefit of UCA application during transtemporal insonation with TCCD. An improvement in the signal quality for the posterior circulation after application of UCA 8,9 was also reported, although the BA could be visualized only over a mean distance of 1.7 cm.…”
Section: Discussionsupporting
confidence: 80%
“…141 Compared with the temporal bone window, use of the lateral frontal bone window appears to increase the detection of intracranial cross-flow patterns via the PCoA. 128 Limited data suggest that intracranial stenoocclusive disease, 26,[130][131][132][133] including Ͼ50% diameter reduction stenosis 27 or distinction between vessel patency or occlusion with reduced flow velocity, 132,133 can be detected more reliably with contrastenhanced TCCS than with TCD. TCCS can demonstrate areas of parenchymal hypoechogenicity in the MCA distribution suggestive of ischemic cerebral infarction shown on brain CT scan, accompanied by abnormal blood flow velocity pattern, with fair to good sensitivity and specificity.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
“…136,137 However, if non-contrast-enhanced TCCS does not reveal any intracranial structures such as the midbrain or any cerebral artery, then contrast-enhanced TCCS will not be diagnostically conclusive. 130,133 A recent power-based TCCS study of 687 consecutive patients 138 showed that an indication for use of an ECA was present in 8.8% of cases. There was a diagnostic result in 75% of cases during transtemporal insonation and 81% of cases during transforaminal insonation.…”
Section: R E T I R E D R E T I R E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous injection of an ultrasound contrast agent (USCA) that is not eliminated via the lungs (eg, Levovist) considerably improves the quality of the Doppler signal even if penetration of the temporal bone is poor. [5][6][7][8][9][10] Therefore, it seemed to be logical to perform the TCD-CO 2 test with such an agent. The effect of a single-bolus injection is only of short duration.…”
mentioning
confidence: 99%